Estimation of size of sella turcica using computed tomography in patients visiting a tertiary care center in Kaski district - Paudel, Nawaraj; Sharma, Pujan; Sharma, Keshab; Parajuli, Santwana; Timilsina, Krishna; Gurung, Kismat (Journal of Gandaki Medical College-Nepal, 2025)
Introduction: Sella turcica is a saddle-shaped depression in the body of the sphenoid bone. The deformity in sella turcica size indicates an abnormality within the cranium. Thus, the objective of the study was to estimate the normal size of sella turcica in Nepalese population using computed tomography and to determine whether its’ size varies with age and sex. Methods: A cross-sectional analytical study was conducted among 250 patients visiting Department of Radiology, Gandaki Medical College from April 11 to July 12, 2024. The patients advised for computed tomography of head were enrolled in the study. The demographic data and sizes (length, anteroposterior diameter and depth) of sella turcica were recorded. Univariate analysis including frequencies and percentage for demographic data and size of sella turcica were calculated. ANOVA test was used to determine the association between size of sella turcica with age groups. Independent t-test was used to determine association of size of sella turcica with gender where p-value <0.05 was considered statistically significant. Results: The mean length, antero-posterior diameter and depth of sella turcica was found to be 10.94±6.90 mm, 12.42±2.26 mm and 7.99±1.49 mm respectively. There was statistically significant increase in length and anteroposterior diameter of sella turcica with age (p<0.05). All the dimensions of sella turcica were highest for males which was not significant. Conclusions: The mean length, antero-posterior and depth of sella turcica was 10.94 mm, 12.42 mm, and 7.99 mm respectively. Furthermore, the length and antero-posterior diameter of sella turcica increased with age while all dimensions of sella turcica didn’t vary with respect to gender.